Availability And Utilization of Physical Facilities as Correlates of Students’ Academic Performance in Electrical Installation and Maintenance Work Practice in Technical Colleges in Ekiti State (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
This study determined the availability and utilization of physical facilities as correlates of students’ academic performance in electrical installation and maintenance work practice in technical colleges in Ekiti State. Four research questions and three null hypotheses guided the study. Descriptive survey and correlational research designs was used for the study. Eight hundred and fifty-three (818 students and 35 teachers) of electrical installation in the six government-owned technical colleges in Ekiti State were studied without sampling. The Instruments for data collection included checklist, structured questionnaire and performance test. The reliability of the performance test was determined through split-half technique. Spearman-Brown formula was employed for reliability coefficient computation which yielded a reliability coefficient of 0.905.  Percentage, mean, standard deviation and Pearson Product Moment Correlation coefficient were used to answer research questions. The t-test statistical tool was used to test the null hypotheses relating to utilization of instructional facilities while Pearson Product Moment Correlation coefficient was used to test the null hypotheses relating to physical facilities and students’ academic performance. Findings revealed that majority of physical facilities are available for electrical installation and maintenance work practice in technical colleges in technical colleges in Ekiti State.  The study also revealed that there is high positive relationship of 0.61 existing between students’ utilization of physical resources and their academic performances in electrical installation and maintenance work practice in technical colleges in Ekiti State. The study concluded that the level of availability and utilization of physical facilities for electrical installation and maintenance work practice in technical colleges in technical colleges in Ekiti State is not adequate for equipping students with practical skills for self-reliance. The study recommended among others that owners of technical colleges in Ekiti State should adequately provide relevant physical facilities for effective teaching of electrical installation and maintenance workshop practices.